An assessment on the role of endophytic microbes in the therapeutic potential of Fagonia indica - Lubna Rahman; Zabta K. Shinwari; Irum Iqrar; Lutfur Rahman; Faouzia Tanveer (BMC, 2017)
Abstract Background Natural products of animals, plants and microbes are potential source of important chemical compounds, with diverse applications including therapeutics. Endophytic bacteria that are especially associated with medicinal plants presents a reservoir of therapeutic compounds. Fagonia indica has been recently investigated by numerous researchers because of its striking therapeutic potential especially in cancer. It is also reported that endophytes play a vital role in the biosynthesis of various metabolites; therefore we believe that endophytes associated with F. indica are of crucial importance in this regard. The present study aims successful isolation, molecular identification of endophytic bacteria and their screening for bioactive metabolites quantification and in vitro pharmacological activities. Methods 16S rRNA gene sequencing was used for the identification of isolated endophytic bacteria. Methanolic extracts were evaluated for total phenolic contents (TPC), total flavonoids contents (TFC), DPPH free radical scavenging activity, reducing power and total anti-oxidant assays were performed. And also screened for antibacterial and antifungal activities by disc diffusion method and their MIC were calculated by broth dilution method using microplate reader. Further, standard protocols were followed for antileishmanial activity and protein kinase inhibition. Analysis and statistics were performed using SPSS, Table curve and Origin 8.5 for graphs. Results Bacterial strains belonging to various genera (Bacillus, Enterobacter, Pantoea, Erwinia and Stenotrophomonas) were isolated and identified. Total phenolic contents and total flavonoids contents varies among all the bacterial extracts respectively in which Bacillus subtilis showed high phenolic contents 243 µg/mg of gallic acid equivalents (GAE) and Stenotrophomonas maltophilia showed high flavonoids contents 15.9 µg/mg quercitin equivalents (QA), total antioxidant capacity (TAC) 37.6 µg/mg of extract, reducing power (RP) 206 µg/mg of extract and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity with 98.7 μg/mL IC50 value. Although all the extracts tested were active to inhibit growth of selected pathogenic microbes (bacteria and fungi), but significant antibacterial activity was observed against Klebsiella pneumonia and B. subtilis. An Enterobacter cloaca was active against Leishmania tropica with IC50 value of 1.4 µg/mg extracts. B. subtilis and Bacillus tequilensis correspondingly exhibit significant protein kinase inhibition of 47 ± 0.72 and 42 ± 1.21 mm bald zones, indicating anti-infective and antitumor potential. Conclusions Our findings revealed that crude extracts of selected endophytic bacteria from F. indica possess excellent biological activities indicating their potential as an important source of antibiotics (antifungal, antibacterial) compounds.